The Flight from Rome [videorecording] - Dault, Gary Michael; Garwood, Joseph J.; McGreevy, John.; Puncher, Jennifer; Ustinou, Peter Sir.; John McGreevy Productions Limited; Multimedia Entertainment (New York Multimedia Entertainment, 1993)
Gripped by darkness and turmoil, Europe was hungry for a spiritual awakening. Travel the continent with Sir Peter and observe how Christianity answered the call. Meet Charlemagne, the englightened monarch who embraced the Christian faith, and St. Francis of Assissi who founded the Franciscan orders. Introduces also St. Catherine of Sienna, the nun whose miraculous vision brought the papacy back to Rome.
Documentary.
VHS.
Editor, Christopher Sumpton.
Jacques Godin as Charlemagne, Andrea Prodan as St. Francis of Assissi, Amy Wela as St. Catherine of Science.
Keywords: Catherine of Science -- Saint; Charlemagne,Emperor -- 742-814.; Francis of Assissi,Saint -- 1182-1226.; Vatican Palace (Vatican City); Catholic church -- Government -- History; Civilization, Medieval; Papacy -- History